Ein Extremalindikator für die ganzen Funktionen mit positiven Nullstellen - Kondratjuk, A. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. А. Кондратюк. Экстремальный индикатор для целых функций с положительными нулямиA. Kondratiuk. Sveikos funkcijos su teigiamais nuliais ekstremalinis indikatorius